2016
DOI: 10.1182/blood.v128.22.3389.3389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surveillance Stool Culture Guided Selection of Antibiotics in Allogeneic Hematopoietic Stem Cell Transplant Patients

Abstract: INTRODUCTION Allogeneic stem cell transplant (allo-SCT) patients are at high risk for severe life threatening bacterial infections. Although the prevalence and pattern of resistance varies among centres and countries, there is a growing global problem of resistance to antibiotics. The consequent increased use of broad spectrum antibiotics and injudicious antibiotic policies have contributed to the selection of multidrug resistant (MDR) pathogens. Translocation of organisms which normally coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In our study as well, the proportion of CRBSI due to GNB was higher (83%) compared to majority of the previously published literature . Such high rates of GNB in our study could be related to the translocation of GNB from the gastrointestinal tract due to mucosal injury associated with the transplant conditioning regimens …”
Section: Discussionsupporting
confidence: 55%
“…In our study as well, the proportion of CRBSI due to GNB was higher (83%) compared to majority of the previously published literature . Such high rates of GNB in our study could be related to the translocation of GNB from the gastrointestinal tract due to mucosal injury associated with the transplant conditioning regimens …”
Section: Discussionsupporting
confidence: 55%
“…In our study it was observed that 28(93.3%) patients recovered from febrile neutropenia in both case and control group and the different was not statistically significant (p>0.05) between two groups. Paul, et al [1] also found in his study there was no significant different in infection related mortality between two groups.…”
Section: Resultsmentioning
confidence: 59%
“…The difference was not statistically significant (p>0.05) between two groups. Paul, et al [1] observed in their study in median age was 26 years (range 3-57) years. In this study majority patients 56.7% were male in cases (surveillance based) and 50% in control group (Empirical)…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations